GmSALT3, Which Confers Improved Soybean Salt Tolerance in the Field, Increases Leaf Cl- Exclusion Prior to Na+ Exclusion But Does Not Improve Early Vigor under Salinity - Liu, Ying; Yu, Lili; Qu, Yue; Chen, Jingjing; Liu, Xiexiang; Hong, Huilong; Liu, Zhangxiong; Chang, Ruzhen; Gilliham, Matthew; Qiu, Lijuan; Guan, Rongxia (Frontiers in Plant Science, 2016)
Soil salinity reduces soybean growth and yield. The recently identified GmSALT3 (Glycine max salt Tolerance-associated gene on chromosome 3) has the potential to improve soybean yields in salinized conditions. To evaluate the impact of GmSALT3 on soybean performance under saline or non-saline conditions, three sets of near isogenic lines (NILs), with genetic similarity 95.6-99.3% between each pair of NIL-T and NIL-S, were generated from a cross between two varieties, 85-140 (salt-sensitive, S) and Tiefeng 8 (salt-tolerant, T) by using marker-assisted selection. Each NIL; 782-T, 820-T and 860-T, contained a common ~1000 kb fragment on chromosome 3 where GmSALT3 was located. We show that GmSALT3 does not contribute to an improvement in seedling emergence rate or early vigour under salt stress. However, when 12-day-old seedlings were exposed to NaCl stress, the NIL-T lines accumulated significantly less leaf Na+ compared with their corresponding NIL-S, while no significant difference of K+ concentration was observed between NIL-T and NIL-S; the magnitude of Na+ accumulation within each NIL-T set was influenced by the different genetic backgrounds. In addition, NIL-T lines accumulated less Cl– in the leaf and more in the root prior to any difference in Na+; in the field they accumulated less pod wall Cl– than the corresponding NIL-S lines. Under non-saline field conditions, no significant differences were observed for yield related traits within each pair of NIL-T and NIL-S lines, indicating there was no yield penalty for having the GmSALT3 gene. In contrast, under saline field conditions the NIL-T lines had significantly greater plant seed weight and 100-seed weight than the corresponding NIL-S lines, meaning GmSALT3 conferred a yield advantage to soybean plants in salinized fields. Our results indicated that GmSALT3 mediated regulation of both Na+ and Cl– accumulation in soybean, and contributes to improved soybean yield through maintaining a higher seed weight under saline stress.